The Effect of Agrobost Biofertilizer on the Growth and Productivity of Potato (Solanum tuberosum) Variety Granola L - Nira Hadayanti (Universitas Muhammadiyah Sidoarjo, 2021)
Potato is a staple food substitute that has a high consumption value. Potato productivity in Indonesia is still inadequate, especially for high-quality seeds. Agrobost is a biological fertilizer that contains microorganisms that can help provide nutrients for plants and can increase the productivity of potato plants. This study aims to determine the effect and optimum dose of agrobost biofertilizer on the growth and productivity of potato (Solanum tuberosum) Granola L variety. The research design used was a non-factorial randomized block design (RAK) with 6 levels of dose treatment and 4 repetitions. The doses used were 0 ml (d0/control), 5 ml (d1), 10 ml (d2), 15 ml (d3), 20 ml (d4), and 25 ml (d5). Parameters observed were plant height, number of leaves, plant wet weight, plant dry weight, total number of tubers, and total weight of tubers. The data obtained quantitatively were analyzed using analysis of variance (ANOVA) followed by a 5% honest real difference test (BNJ). It was found that the application of Agrobost biofertilizer had a significant effect on the weight of potato tubers but had no significant effect on plant height, number of leaves, fresh weight and dry weight of plants and the number of potato tubers. Agrobost biofertilizer with a dose of 20 ml/L produced the highest average tuber weight, which was 7.71 grams.